Geotechnical soil mapping from electrical and mechanical properties: Case study of the Bafoussam urban area, west Cameroon. (March 2022) - Malick Rosvelt, Demanou Messe; Jean Victor, Kenfack; Isaac yannick, Bomeni; François, Ngapgue; Armand Sylvain Ludovic, Wouatong
Abstract: Preliminary work in civil engineering works often involves the investigation of soil support in order to secure or predict project safety. The objective of this work is to purpose an urban geotechnical soil map combining physical and mechanical behaviour of the soil and its electrical properties. Field work with auger corer allowed collection of samples for analysis. The results of the Atterberg limits and particle size analysis enabled classification of those soils according to HRB as silty or clayey gravels and sands (class A-2-7) and clayey soils (A-7-5). The Casagrande Plasticity Diagram classifies them as At and Lt (very plastic clays and silts) and the GTR classifies them as sandy and gravelly soils with fines (B6) and fine clay soils (A2 and A3). These classifications show that the study area is mainly covered by sandy-clay, lateritic clay and lateritic gravelly soils. The iso-resistivity maps and resistivity sections made from the results of vertical electrical soundings, allow the identification of three ranges of resistivity: a low resistivity less than 300 Ώ.m, a medium resistivity range between 300 and 500 Ώ.m and a high resistivity greater than 500 Ώ.m. These ranges of resistivity correspond to the different formation disparities that make up the subsurface. Associated penetrograms show these soils are very resistive in the cuirass subsurface zones with very compact formations with permissible stress values between 2.5 and 5.2 bars. At greater depths, these values are moderate in the clayey sands with stresses between 0.8 and 3 bars and low in the clays and lateritic soils (˂1 bar). The application of determination coefficient (R 2 ) and Spearman correlation (rs ) between permissible stress and true resistivity gives values of 0.79 and 0.74 respectively. There is a good qualitative and quantitative correlation between these two parameters in the study area. The superimposition and comparison of the different results with the geological formations enables development of a geotechnical soil map. This map enables us to understand the lithological and mechanical heterogeneity of the soils during the construction of structures in the urban perimeter of Bafoussam. Highlights: Soil map of the study area is proposed. Vertical electrical soundings give a general indication of the soil distribution on the lateral plane according to the depth. The dynamic penetrometer soundings determine the cone resistance of these soils and allow to draw an iso-stress map of the sector. The correlation between the different methods gives a Spearman correlation coefficient higher than 0.7, characteristic of a good correlation. The geotechnical map of the soils of the urban perimeter of Bafoussam is proposed.